Central Asia in transition - Rumer, Boris (ed.) (Delhi, 2003)
One of the more significant developments in international affairs in the last decade has been the formation of five newly independent states in Central Asia. Because of their geostrategic importance and natural resources, they have attracted increasing interest in the world political community. These countries have become a kind of mecca for foreign dignitaries and leaders, who have continuously visited this region since the disintegration of the Soviet Union in 1991. Central Asia has elicited enormous attention in the world's mass media; suffice it to say that, of the fifty-two issues of the Economist in 1994, nineteen of them contained articles on Central Asia. A substantial number of books dealing with the political, social, and ethnic problems of the region also have appeared. As a result, there is a veritable flood of information about Central Asia-reports about its exotica and incalculable natural wealth, predictions of the inexorable spread of Islamic fundamentalism, dire warnings of inter-ethnic fratricide and an imminent Malthusian catastrophe, conflicts over the allocation and distribution of resources, ecological problems and desiccation of the Aral Sea, liquidation of nuclear weapons stationed there, the production and trans-shipping of narcotics.
Keywords: Economic development-Central Asia